Innovative approaches for amino acid production via consolidated bioprocessing of agricultural biomass - Chu, Pei Hsia; Jenol, Mohd Azwan; Phang, Lai Yee; Ibrahim, Mohamad Faizal; Purkan, Purkan; Hadi, Sofijan; Abd Aziz, Suraini (Springer, 2024)
Agricultural plantations in Indonesia and Malaysia yield substantial waste, necessitating proper disposal to address environmental concerns. Yet, these wastes, rich in starch and lignocellulosic content, ofer an opportunity for value-added product development, particularly amino acid production. Traditional methods often rely on costly commercial enzymes to convert biomass into fermentable sugars for amino acid production. An alternative, consolidated bioprocessing, enables the direct conversion of agricultural biomass into amino acids using selected microorganisms. This review provides a comprehensive assessment of the potential of agricultural biomass in Indonesia and Malaysia for amino acid production through consolidated bioprocessing. It explores suitable microorganisms and presents a case study on using Bacillus subtilis ATCC 6051 to produce 9.56 mg/mL of amino acids directly from pineapple plant stems. These fndings contribute to the advancement of sustainable amino acid production methods using agricultural biomass especially in Indonesia and Malaysia through consolidated bioprocessing, reducing waste and enhancing environmental sustainability.